Inductive tools for connected delta-matroids and multimatroids. (June 2017) - Chun, Carolyn; Chun, Deborah; Noble, Steven D.
Abstract: We prove a splitter theorem for tight multimatroids, generalizing the corresponding result for matroids, obtained independently by Brylawski and Seymour. Further corollaries give splitter theorems for delta-matroids and ribbon graphs.